(untitled) (Andamios, Revista de Investigación Social, 2012)
The tension between a desire for development and faithfulness to one’s own values —the tension development / ethos—must be considered to be one of Leopoldo Zea’s fundamental concerns. Nevertheless, this tension has been addressed from many different angles, which have proved difficult to reconcile. This essay has two purposes: to show the principle methods which Zea used to formulate this tension, and to map out a series of considerations about the obsolescence/validity of Zea’s legacy —colossal, protean, taut, multifacted— based on a desire to infuse substance and density into some of the most characteristic current debates on the topic.